Real-time observation of bacteriophage T4 gp41 helicase reveals an unwinding mechanism - Lionnet, Timothée (National Academy of Sciences, 2007)
Helicases are enzymes that couple ATP hydrolysis to the unwinding of double-stranded (ds) nucleic acids. The bacteriophage T4 helicase (gp41) is a hexameric helicase that promotes DNA replication within a highly coordinated protein complex termed the replisome. Despite recent progress, the gp41 unwinding mechanism and regulatory interactions within the replisome remain unclear. Here we use a single tethered DNA hairpin as a real-time reporter of gp41-mediated dsDNA unwinding and single-stranded (ss) DNA translocation with 3-base pair (bp) resolution. Although gp41 translocates on ssDNA as fast as the in vivo replication fork (≈400 bp/s), its unwinding rate extrapolated to zero force is much slower (≈30 bp/s). Together, our results have two implications: first, gp41 unwinds DNA through a passive mechanism; second, this weak helicase cannot efficiently unwind the T4 genome alone. Our results suggest that important regulations occur within the replisome to achieve rapid and processive replication.